Solving dissipative nonlinear schrodinger equation with variable coefficient using homotopy perturbation method - Mohd Yazid, Nazatulsyima; Tay, Kim Gaik; Md Sudin, Azila; Choy, Yaan Yee (Medwell Publications, 2017)
This study focuses on the solution of the Dissipative Nonlinear Schrodinger equation with Variable coefficient (DNLSV) by using Homotopy Perturbation Method (HPM) to obtain approximate analytical solution. The procedure of the method is systematically illustrated. The result obtained is then compared with the progressive wave solution to verify the accuracy of the HPM solution. The absolute error of the HPM solution of the DNLSV equation with the progressive wave solution will later be carried out using the 1.1A TLAB Program.